Impact of Government Intervention on Manufacturing Enterprises Innovation level, in Ethiopia - Hayleslasie Tsegay Aregawi; B. C. M Patnaik (Cogent Economics & Finance, 2023)
Besides alert devastation situation of Small Manufacturing Enterprises (SMEs) in the country, what support receives from the government, banking, microFinance institutions, technology transfer and their role in the local economic development are the main issues that need to be addressed. Hence, the main objective of the study is to evaluate the impact of government intervention on the Small Manufacturing Enterprises Innovation level in Tigray, Ethiopia. For this purpose, we conducted a survey of 464 small manufacturing enterprise (textile and garment, metal and wood works, input for construction, chemical products, jewellery, and agro-processing sectors) owners. The study is, stressed the primary data, adopt a Cross-sectional survey study with a mixed research approach, and the types of research are explanatory. Multistage cluster sampling was applied to select each business owner. Descriptive statistics, chi-square test, propensity score matching and logistic regression were relayed for the analysis part with the help of Stata version 12. The average score innovation level of the enterprise is found at 2.89 which is assembled under the low innovators in the sample of the enterprise analyzed. Innovations activity has performed with the highest score level in the customer dimension. With regard to the PSM estimated, government intervention plays a significant role in utilizing innovation and technology transfer. Likewise, in a binary logistic regression, the study found that the intervention of the program has a positive effect on the innovation process dimension. Before and after matching, the findings of both models are similar in terms of the owner's innovation of offering dimension, solution dimension, customer dimension, and value capture, which is positive and significant. Designing a new government policy intervention of Small Manufacturing Enterprises is among the resolutions to be applied by the government for purpose of productivity enhancement, self-employability, sustainability of the business and transforming to produce innovative products to replace imported goods.
Keywords: 330; Government Intervention; Innovation level; Manufacturing Enterprises; Propensity Score Matching